2016
DOI: 10.1177/0394632016672218
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on Emodin alleviating alpha-naphthylisothiocyanate-induced intrahepatic cholestasis by regulation of liver farnesoid X receptor pathway

Abstract: The aim of this study is to investigate Emodin on alleviating intrahepatic cholestasis by regulation of liver farnesoid X receptor (FXR) pathway. Cell and animal models of intrahepatic cholestatis were established. Biochemical tests and histomorphology were performed. The messenger RNA (mRNA) and protein expression of FXR, small heterodimer partner (SHP), uridine diphosphate glucuronosyltransferase 2 family polypeptide B4 (UGT2B4), and bile salt export pump (BSEP) was detected. As a result, compared with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…In vivo study, we used ANIT to establish the rat model of hepatotoxicity (Ding et al, 2016;Xiong et al, 2019) and evaluate the effects of LDHJ granules on intrahepatic cholestasis (Kossor et al, 1993). Consistent with the previously reported findings (Wang et al, 2014), the increased levels of biomarkers (TBA, TBIL, DBIL, AST, ALT, ALP, and g-GT) and abnormal histopathological changes were observed in the liver of young rats with ANIT-induced intrahepatic cholestasis.…”
Section: Hepatocytic Levels Of Apoptosis-related Proteins Involved Insupporting
confidence: 78%
See 2 more Smart Citations
“…In vivo study, we used ANIT to establish the rat model of hepatotoxicity (Ding et al, 2016;Xiong et al, 2019) and evaluate the effects of LDHJ granules on intrahepatic cholestasis (Kossor et al, 1993). Consistent with the previously reported findings (Wang et al, 2014), the increased levels of biomarkers (TBA, TBIL, DBIL, AST, ALT, ALP, and g-GT) and abnormal histopathological changes were observed in the liver of young rats with ANIT-induced intrahepatic cholestasis.…”
Section: Hepatocytic Levels Of Apoptosis-related Proteins Involved Insupporting
confidence: 78%
“…The protective effects of forsythoside-A and chlorogenic acid on cell apoptosis have been reported (Ali et al, 2017;Yan et al, 2017). Our research group has found the rescue activity of emodin on the intrahepatic cholestasis (Ding et al, 2016;Xiong et al, 2019). So forsythoside-A, emodin, chlorogenic acid may be promising in representing the LDHJ for further cell experiments.…”
Section: Hepatocytic Levels Of Apoptosis-related Proteins Involved Inmentioning
confidence: 71%
See 1 more Smart Citation
“…LO2 cells were maintained in RPMI 1640 media supplemented with 10% FBS. As previously described (Ding et al, ), cells were distributed into either six‐well plates for real‐time PCR and Western blotting or 96‐well plates for the CCK8 experiments and preliminary lentiviral transfection experiments for 24 h. When the cell cultures reached 70% density, they were treated with corilagin, UDCA or DEX. After 24 h, the cells were harvested for real‐time PCR and Western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was followed by our past experiment [23, 24]. The expression of TLR-4 and associated signaling molecule proteins were detected by western-blot assay.…”
Section: Methodsmentioning
confidence: 99%